Small Scale Factors Modify Impacts of Temperature, Ice Scour and Waves and Drive Rocky Intertidal Community Structure in a Greenland Fjord - Sejr, Mikael K.; Mouritsen, Kim N.; Krause-Jensen, Dorte; Olesen, Birgit; Blicher, Martin Emil; Thyrring, Jakob (Frontiers in Marine Science, 2021)
Understanding the influence of physical drivers and their scale-dependent interactions on ecosystem structure and function is becoming increasingly relevant as ecologists are challenged to quantify and predict the biological implications of anthropogenic activities and climate changes. Here, we aim to quantify the impact of multiple physical drivers (ice scour, wave expoure and air temperature) and their interactions with small scale modifying factors tidal level, substrate rugosity and canopy forming macroalgae on rocky intertidal community structure. We did this by quantifying intertidal biomass, cover and species richness at three tidal levels (high, mid, low) at four sites in a sub-Arctic Greenland fjord. We found a well-developed intertidal community, with a total of 16 macroalgae and 20 invertebrate species. At one locality, the total biomass was dominated by canopy forming algae exceeding 16 kg wet weight per m-2. Physical stress from ice scour, waves and air exposure had negative effects on all three community metrics but important interactions and modifying processes were identified. The effect of tidal level differed between sites ranging from an absence of organisms at both high- and mid-intertidal level at the most ice- and wave exposed site to extensive cover across all three tidal level at the wave and ice sheltered site. Canopy forming macroalgae and substrate rugosity both modified the impacts of physical stress. In the absence of ice scour, canopy forming algae formed extensive cover that modified extreme air temperatures, and the abundance of dominant invertebrate species were all positively related to the biomass of macroalgae. Rugosity provided refuge from ice scour, facilitating increased species richness and cover at exposed sites. Moreover, we detected no negative effects of fast ice, and ice scour impacts were primarily found where presence of glacial ice was combined with wave exposure. Our results provide an example of how large-scale physical factors pass through a filter of several modifying smaller scale processes before their impact on plot scale community structure is manifested.